Application of the copper(II)-aminosilane catalysts in the oxidative polymerization of 2,6-dimethylphenol - Firlik, S.; Skupiński, W.; Wielgosz, Z.; Stasiński, J. (Polimery, 2015)
The aim of this work was to examine the aminosilane ligands for the copper(II) salts and their application as catalysts for the oxidative polymerization of 2,6-dimethylphenol leading to poly(2,6-dimethyl-1,4-phenylene ether) (PPE) [also known as poly(phenylene oxide) (PPO)] formation. As aminosilane ligands, silane derivatives containing primary and/or secondary amino groups were tested. Among aminosilanes used, PPE was only obtained when N-methylaminopropyltrimetoxysilane (MAPTMS) as a ligand for copper(II) was used. CuCl2 and CuBr2 were compared as catalyst precursors for 2,6-dimethylphenol polymerization and influence of N/Cu molar ratio in the range from 80 to 160 on PPE yield and its Mw was tested. It was observed, that with increasing N/Cu molar ratio from 80 to 120, both PPE yield and Mw increased. PPE with the highest Mw was obtained when CuBr2-MAPTMS as acatalyst was used. At N/Cu molar ratio equal to 160, a decrease in PPE Mw obtained with use of both precursors and decrease in PPE yield for CuCl2-MAPTMS catalyst were noticed. The condensed nanoorganosilicon particles of spherical shape well dispersed in PPE were determined in the polymer matrix. The UV-Vis studies showed that, strong ligand field of the aminosilane ligand easier electron transfer from monomer to Cu(II) and thus polymerization facilitate.